2016
DOI: 10.3892/etm.2016.3947
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and neuroprotective effects of sanguinarine following cerebral ischemia in rats

Abstract: Abstract. Stroke is one of the leading causes of mortality worldwide. Protective agents that can diminish injuries caused by cerebral ischemia-reperfusion (I/R) are important in alleviating the harmful outcomes of stroke. The aim of the present study was to investigate the protective role of sanguinarine in cerebral I/R injury. A rat middle cerebral artery occlusion model was used to assess the clinical effect of sanguinarine, and inflammatory cytokines in the serum were detected by ELISA. Western blotting was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 28 publications
0
23
0
4
Order By: Relevance
“…The beneficial effect of HBO therapy varies with the tumor type, size of the lesion, and malignancy. [304][305][306] Several drugs, e.g., sanguinarine, [307][308][309] glycyrrhizin, 310 piroxicam, [311][312][313] salidroside, [314][315][316] astragaloside, 317,318 and others, [319][320][321][322] are used in both glioma and ischemia treatment due to the counteracting effect of common signaling pathways.…”
Section: Therapeutic Approaches For Ischemia and Gliomamentioning
confidence: 99%
“…The beneficial effect of HBO therapy varies with the tumor type, size of the lesion, and malignancy. [304][305][306] Several drugs, e.g., sanguinarine, [307][308][309] glycyrrhizin, 310 piroxicam, [311][312][313] salidroside, [314][315][316] astragaloside, 317,318 and others, [319][320][321][322] are used in both glioma and ischemia treatment due to the counteracting effect of common signaling pathways.…”
Section: Therapeutic Approaches For Ischemia and Gliomamentioning
confidence: 99%
“…Thus, it is not a coincidence that a prototypical proinflammatory protein such as NF-κB appeared as a presumable master regulator of transcription of genes recognized in microarray-based transcriptomic mRNA expression data. Recently, Wang et al, proved that sanguinarine as anti-inflammatory agent prevented cerebral stroke in vivo via downregulation of the inflammatory cytokines, TNF-α, IL-1β and IL-6 (Wang et al, 2017 ). Moreover, other genes from diverse functional groups appeared in our analysis, such as signal transducers promoting cancer growth ( CD53, RAB33A, GNA11, CANX, OCRL, GIPC1 , and SOS1 ), microtubule formation ( KIF21B ) and cell migration ( ASAP2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown the therapeutic potential of SNG over a range of human pathological and toxicological conditions including cancer; for example, lung cancer [25], cervical cancer [26], gastric cancer [27,28], liver cancer [29,30], multiple myeloma [19], acute lymphoblastic leukemia [31], prostate cancer [32], colorectal cancer [33], ovary cancer [34] and pancreatic cancer [35]. Recently Achkar et al [36] extensively reviewed the anticancer features of SNG and, additionally, antioxidant/anti-inflammatory [37][38][39], antifungal [40,41], antibacterial [42,43], anthelmintic [44] and other pharmacological activities of SNG have also been reported. SNG has been shown to suppress stemness of pancreatic cancer stem cells [45] and, interestingly, also to exert anticarcinogenic potential via modulating expression and functioning of noncoding RNAs [28,34].…”
Section: Introductionmentioning
confidence: 99%